Site Specific Nitrogen Management Simulated by CropSyst Model under Different Inputs of Nitrogen Fertilizer - Wijayanto, Yagus (UNIVERSITY OF LAMPUNG, 2010)
Site Specific Nitrogen Management Simulated by CropSyst Model under Different Inputs of Nitrogen Fertilizer (Y Wijayanto): Site Specific Nutrient Management (SSNM) has been suggested as the only means for increasing productivity of crops and minimizing the environmental impacts. Despite of this, it is also widely recognized that compared to uniform application, SSNM provides a significant challenges related to the level of management. This is due to the fact that SSNM relates to the management of field / site (or fields / sites) and considers also the spatial and temporal component of factors leading to crop production. A method is urgently required and the most appropriate one is crop model. This study was aimed at using CropSyst to model yields due to the difference in N applications and its implementation for SSNM. The study area was located at Jenggawah Village, Sub-District Jenggawah, Jember Regency. Thirty soil samples were taken and six farmer’s fields were chosen for the purpose of modeling. Interview was conducted to obtain the information about the management of farmer’s fields. Yields in each farmer’s fields were used as an integrated indicator. The results suggested that the predicted yields at farmer’s fields were in agreement with those in reality. Simulated yields based on different amount of N inputs showed yields were proportional with different N inputs. This study concluded that there do exist a significant amount of potential applications of CropSyst for Site Specific Nitrogen Management